2019
DOI: 10.1038/s41598-019-50674-3
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol affects Zika virus replication in vitro

Abstract: Zika virus (ZIKV) infection is a serious public health concern. ZIKV infection has been associated with increased occurrences of microcephaly among newborns and incidences of Guillain-Barré syndrome among adults. No specific therapeutics or vaccines are currently available to treat and protect against ZIKV infection. Here, a plant-secreted phytoalexin, resveratrol (RES), was investigated for its ability to inhibit ZIKV replication in vitro. Several RES treatment regimens were used. The ZIKV titers of mock- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 59 publications
(55 reference statements)
0
36
0
1
Order By: Relevance
“…Resveratrol is a well-known powerful activator of sirtuins [ 101 ]. Recent work demonstrated that addition of this compound to cell culture pre- and post- exposure to ZIKV reduced the viral load from 30% to 90%, respectively, showing another promising venue of sirtuins as viral inhibiting agents [ 102 ]. The bacterial sirtuin CobB, a homolog of Escherichia coli sirtuin negatively impacted the growth of both bacteriophages T4 and λ [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is a well-known powerful activator of sirtuins [ 101 ]. Recent work demonstrated that addition of this compound to cell culture pre- and post- exposure to ZIKV reduced the viral load from 30% to 90%, respectively, showing another promising venue of sirtuins as viral inhibiting agents [ 102 ]. The bacterial sirtuin CobB, a homolog of Escherichia coli sirtuin negatively impacted the growth of both bacteriophages T4 and λ [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a non-flavonoid present in trace quantities, is a natural antioxidant and anti-inflammatory compound, known to play a key role in immunoregulation, metabolic syndrome, cardiovascular, neuroprotection, and cancer treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. It has also received attention due to its antimicrobial activity against bacterial, fungal, and viral species in vitro [ 21 , 22 , 23 , 24 ].…”
Section: Introduction: An Overview Of Wine To the Past From The Prmentioning
confidence: 99%
“…In the contrary, MERS-CoV is also activated by furin, a serine endoprotease that has been implicated in the processing of fusion proteins and cell entry of other RNA viruses, including HIV, avian influenza A/H5N1 virus, Ebola virus, Zika virus, Marburg virus and flaviviruses 70 . Resveratrol potently inhibit almost all the above mentioned viral replications in the host cells but not their entry 63,71,72,73,74,75,76,77,78 . In this regard, we strongly recommend further animal studies are necessary before considering resveratrol for clinical trials.…”
Section: Resveratrol a Potential Drug To Human Coronaviruses (Covs) Wmentioning
confidence: 97%